Connecting High School Students With Nature – How Different Guided Tours in the Zoo Influence the Success of Extracurricular Educational Programs - Kleespies, Matthias Winfried; Gübert, Jennifer; Popp, Alexander; Hartmann, Nicola; Dietz, Christian; Spengler, Tanja; Becker, Martin; Dierkes, Paul Wilhelm (Frontiers in Psychology, 2020)
Zoos attract millions of visitors every year, many of whom are schoolchildren. For this reason, zoos are important institutions for the environmental education of future generations. Empirical studies on the educational impact of environmental education programs in zoos are still rare. To address this issue, we conducted two studies: In study 1, we investigated students’ interests in different biological topics, including zoos (n = 1587). Data analysis of individual topics revealed large differences of interest, with advanced students showing less interest in zoos. In study 2, we invited school classes of this age group to visit different guided tour at the zoo and tested connection to nature before and after each educational intervention (n = 608). The results showed that the guided tours are an effective tool to raise students’ connection to nature. Add-on components have the potential to further promote connection to nature. The education programs are most effective with students with a low initial nature connection.